Gastrointestinal hemorrhage due to neurofibromatosis type 1: A case report - Gamarra Osorio, Elman Rolando (2020)
We present the case of a 40-year-old male with a previous diagnosis of neurofibromatosis and a chronic history of intermittent rectal bleeding episodes. He visited the emergency service for frequent rectal bleeding associated with hypotension and tachycardia, and was hospitalized. Complementary tests evidenced grade 1 internal hemorrhoids not associated with the clinical features of the patient. Due to the intermittent nature of the bleeding, a vascular malformation was suspected, which was subsequently confirmed by a pelvic and abdominal angiography.